PENGEMBANGAN MODUL BIMBINGAN DAN KONSELING UNTUK PENGELOLAAN STRES AKADEMIK SISWA KELAS XI SMAN 1 SAGULING - Indiriani, Firawati; Fatimah, Siti; Septian, Muhammad Rezza (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to determine the process of developing, guiding, and the effectiveness of modules and counseling for managing students' academic stress. The research method used is R&D (Research and Development) with the Borg and Gall development model developed by Sugiyono. Analysis of the data used is for qualitative data using the steps of describing, classifying/categorizing, and connecting while for quantitative data using descriptive and inferential statistics. The subjects of this study consisted of material experts, media experts, practitioners, and class XI students of SMAN 1 Saguling. The results showed that the development process was carried out through 9 stages including (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision, (8) use trial, (9) product revision. Then rely on the developed module, namely media experts by 95%, media experts by 100%, students during trials by 85%, students during trials by 90%. So that from the five assessments the module developed is included in the "Very Worthy" category. Then for the effectiveness of the developed module, it shows the value of sig. (2-tailed) 0.000 <0.05, then Ho is rejected and Ha is accepted. So that the module developed is effective in managing academic stress for class XI students of SMAN 1 Saguling.